CANDI GUNUNG KAWI SEBAGAI SUMBER BELAJAR SEJARAH : PENERAPAN PENDEKATAN LIVING HISTORY LEARNING UNTUK PENGUATAN LITERASI HISTORIS SISWA - dzakiyya annisa balqis (Universitas Negeri Semarang, 2026)
Low historical literacy among students’ has become a significant problem in history education, especially when learning processes still emphasize memorization of facts, figures, and chronological sequences. As a result, students are less accustomed to reading historical evidence, understanding past contexts, and connecting historical events with contemporary social life. This study aims to examine the utilization of Gunung Kawi Temple as a history learning resource through a Living History Learning approach to strengthen students’ historical literacy more deeply. The study uses a qualitative approach with a contextual case study design. The research location is in the Gunung Kawi Temple area, Gianyar Regency, Bali, which serves as a representative study site. Informants consisted of two tour guides and three local residents selected purposively because they are considered to have comprehensive knowledge of the site’s history, culture, and social function. Data were collected through direct observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model through stages of data condensation, data display, and drawing conclusions systematically. The results indicate that Gunung Kawi Temple has great potential as a history learning resource because it contains historical, cultural, religious, and educational values simultaneously. Through direct visits, students can observe the cliff temple forms, understand traces of the ancient Balinese civilization, and witness the living cultural continuity within the surrounding community concretely. However, the site’s utilization still faces challenges, such as limited educational information, the dominance of tourism functions, and students’ limited prior understanding of local history. Thus, Gunung Kawi Temple can be utilized as a living history laboratory that supports more contextual, reflective, and meaningful history learning